A new automated system for the preparation of sclerosant foam: A study of the physical characteristics produced and the device settings required. (October 2020) - Roche, Enric; Pons, Ramon; Roche, Oriol; Puig, Antoni
Objectives: To determine the quality of sclerosant foam produced with an automated preparation system with multiple combinations of sclerosing agents, gases, and device settings. Methods: Single-use mixing capsules filled with air or O2 /CO2 and polidocanol (0.25, 1, or 3%) or sodium tetradecyl sulfate (0.2 or 1%) were coupled to a customized magnetic stirrer. Stirring speed and time were adjusted between 1500 and 4000 r/min and 30 and 60 s, respectively, and characteristics of the foam produced were measured: half-life, bubble diameter, and gas-to-liquid ratio. Results: With optimized device settings, the following foam characteristics were obtained: half-life range, 1.4 ± 0.9 to 5.2 ± 0.6 min; bubble diameter, 84 ± 14 to 119 ± 6 µm; and gas-to-liquid ratio, 5:1–7:1. Sodium tetradecyl sulfate foam was quicker to form than polidocanol but faster to degrade. Foams with low sclerosant concentrations and O2 /CO2 required higher speed and longer time. Conclusions: Suitable foam characteristics could be obtained with all combinations of sclerosing agent, concentration, and gas.